Angiographic Comparison of Coronary Artery Disease between Diabetic Men and Women (Cardiovascular Journal, 2013)
Background: Cardiovascular diseases are the leading cause of death and morbidity in diabetic patients and this group is two to four times as likely to develop cardiovascular disease than the nondiabetic group, women being specially involved in this situation. In women , diabetes appear to be a stronger risk factor for the development of coronary heart disease than in men regardless of age ,menopausal status and whether or not the patient is insulin or non-insulin dependent. Objective of this study was to compare the angiographic extent of coronary artery disease between diabetic men and diabetic women. Method: This observational study was undertaken on 100 diabetic patients ( 50 women and 50 men) admitted inNational Institute of Cardiovascular disease (NICVD) during the period of July, 2006 to April ,2007.Diabetic women with coronary artery disease constitute the study group-I and diabetic men with coronary artery disease matched for age (±5 years) and risk factors , the study group-II . Coronary angiography was done in all patients & findings were analyzed. Segmental distribution method for coronary artery lesions was used to describe the distribution of atherosclerotis in coronary artery. Results: The mean age of group I was 51.02 ±8.93 years and that of the group II was 50.99± 9.83 years. In this study it was found that Diabetic women with coronary artery disease (CAD) had a higher coronary artery score, CAS (11.02±5.034) as compared to the diabetic men with CAD ( 8.04±4.866) (p